2020
DOI: 10.1093/sleep/zsaa004
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sleep apnea responses to oral appliance therapy using polysomnographic airflow

Abstract: Study Objectives Oral appliance therapy is an increasingly common option for treating obstructive sleep apnea (OSA) in patients who are intolerant to continuous positive airway pressure (CPAP). Clinically applicable tools to identify patients who could respond to oral appliance therapy are limited. Methods Data from three studies (N = 81) were compiled, which included two sleep study nights, on and off oral appliance treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…9 Our findings confirm the results obtained with NSE showing that inspiratory discontinuity, quantified as high NED, characterizes epiglottic collapse. 4,10 The distinction between tongue base and other collapse types shown with NSE 4 was absent in the current dataset. It is important to note, however, the difference in tongue base collapse scoring between the NSE studies and the current DISE study.…”
Section: Chestjournalorgmentioning
confidence: 66%
See 2 more Smart Citations
“…9 Our findings confirm the results obtained with NSE showing that inspiratory discontinuity, quantified as high NED, characterizes epiglottic collapse. 4,10 The distinction between tongue base and other collapse types shown with NSE 4 was absent in the current dataset. It is important to note, however, the difference in tongue base collapse scoring between the NSE studies and the current DISE study.…”
Section: Chestjournalorgmentioning
confidence: 66%
“… 9 Our findings confirm the results obtained with NSE showing that inspiratory discontinuity, quantified as high NED, characterizes epiglottic collapse. 4 , 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary analysis of respiratory events were based on the ensemble-averaging method1 30 31: within a patient, flow and drive signals from each event were aligned at event termination, overlaid and mean-averaged. Flow-drive correlation ( R ), flow:drive and Δdrive/Δflow were determined from the ensemble event.…”
Section: Methodsmentioning
confidence: 99%
“…The same research group also identified expiratory flow limitation (recognizable as pinching of the airflow signal) as the hallmark of palatal prolapse ( 29 ). According to recent evidence, this pinching feature is associated with a negative response to mandibular advancement device treatment, indicating the potential of this non-invasive assessment ( 32 ).…”
Section: Introductionmentioning
confidence: 99%